Modalidad de trabajo y su relación con la satisfacción laboral de los trabajadores administrativos de la Municipalidad Distrital de Moche, 2018. - Azabache Aguilera, Maria del Carmen (2019)
ABSTRACT The present research called “Modality of work and its relationship with the job satisfaction of administrative workers of the District Municipality of Moche 2018” is raised due to the important role that district municipalities or local governments are contributing to the development and economy of the country, as well as the achievement of its objectives. For this, the appropriate, motivated and satisfied personnel must be available; Thus, it is proposed to study the relationship between the work modality and job satisfaction in the District Municipality of Moche. The research is of the descriptive and correlational type, the same that was carried out in a sample of 39 workers of the institution under study. To measure job satisfaction, a questionnaire of 21 questions is needed on the Likert scale, which is grouped into 04 factors: self-realization, compensation, work environment and communication. As a result, it showed that there is a significant relationship between the work modality and the level of job satisfaction, being able to specify a MEDIUM relationship.